(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
The final document of the cultural committee at the Bandung Conference emphasized that Asia and Africa is thebirthplace of great civilizations. Modern cultural tourism has helped the world to discover many of their treasures.Colonialism tended to give Asia and African an undeserved inferiority complex. Social science has raised ourconsciousness about the dangers of ethnocentricity and the recognition of multiple intelligences. Unlike rawmaterials and other materials extracted by colonial power, culture is an intangible asset that cannot be stolen.Independence proved to be a necessary but not sufficient condition for the development of the Global South. Muchof it is still materially poor yet culturally rich. Globalization has made these riches more available to bothinternational and domestic tourists. Intellectual property rights now protect these riches. Cultural tourismincludes music, dance, handicraft, dress, architecture, gastronomy, agriculture and religion. Although they can beused for commercial purposes in international tourism, they can also be used by local people to increase theirnational pride and build their nation. This results in a Win-Win situation instead of neocolonialism.